2012
DOI: 10.1007/s11442-012-0929-y
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a conversion from grassland to cropland on the different soil organic carbon fractions in Inner Mongolia, China

Abstract: Cultivation is one of the most important human activities affecting the grassland ecosystem besides grazing, but its impacts on soil total organic carbon (C), especially on the liable organic C fractions have not been fully understood yet. In this paper, the role of cropping in soil organic C pool of different fractions was investigated in a meadow steppe region in Inner Mongolia of China, and the relationships between different C fractions were also discussed. The results indicated that the concentrations of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 37 publications
1
11
0
Order By: Relevance
“…Secondly, cropland upper soil carbon is easily taken away by the wind, especially during spring, due to surface bareness. Our result is in good agreement with a previous study conducted in the Xilin River Basin of Inner Mongolia that reported the stored total organic carbon in the uppermost 30 cm soil layer was greater in the grassland than in the cropland (Qi et al, 2012).…”
Section: Comparison Of Soc Stocks Among Land Use Typessupporting
confidence: 93%
“…Secondly, cropland upper soil carbon is easily taken away by the wind, especially during spring, due to surface bareness. Our result is in good agreement with a previous study conducted in the Xilin River Basin of Inner Mongolia that reported the stored total organic carbon in the uppermost 30 cm soil layer was greater in the grassland than in the cropland (Qi et al, 2012).…”
Section: Comparison Of Soc Stocks Among Land Use Typessupporting
confidence: 93%
“…The belowground biomass of the spring wheat field decreased by 98%, which mainly accounts for the loss of SOC under cultivation treatment. Additionally, the amount of SOC stock was also decided by the balance between the decomposition of SOC and the input of organic carbon to the soil from the plant residues or litter [14]. In this study, with plant biomass being harvested or removed, the total nitrogen content of the soil significantly declined, leading to a lower C:N ratio at both soil depths under grazing and cultivation treatments.…”
Section: Effects Of Grazing and Cultivation On Soc Stockmentioning
confidence: 84%
“…The Xilin River Basin is the major base of livestock husbandry in China. There was practically no human activity in this region before the 1950s, and the first extensive cultivation started in 1953 [14]. Meanwhile, the grazing intensity was at a very low level until the grasslands were thrown open to private use in 1978.…”
Section: The Study Areamentioning
confidence: 99%
“…Additionally, as revealed in this study, agricultural intensification and expansion occurred in some parts of IM since the early 2000s. Although they could contribute to improving AGB locally, some previous studies have demonstrated that reclamation for cultivation in arid and semi-arid environments could potentially lead to land degradation through degrading soil properties [69,70] and lowering groundwater levels [71]. Therefore, this issue should also be sufficiently emphasized and properly addressed in the future.…”
Section: Implications For Regional Sustainabilitymentioning
confidence: 99%